Effectiveness of various sterilization methods of contaminated post-fitted molar band - Anggia Tridianti; Krisnawati Krisnawati; Nia Ayu Ismaniati (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2013)
Background: Molar band as anchoring device may be contaminated during the fitting process. Thus, decontamination process is essential to prevent cross-infection between patients. Purpose: The objective of this research was to determine the amount of bacteria in molar band post-fitted on the patient teeth, after previously undergone pre-sterilization using alcohol and ultrasonic cleaning bath followed by sterilization using dry heat oven and steam autoclave, in order to find the best method in decontamination of post-fitted molar band. Methods: Four molar bands which already fitted on one patient then divided evenly into two groups. The first group was pre-sterilized using alcohol. One of the bands then sterilized using dry heat oven, while the other one was sterilized using steam autoclave. The second group was pre-sterilized using ultrasonic cleaning bath. One band from this group then sterilized using dry heat oven and the other was sterilized using steam autoclave. The next step was to immerse all the bands in a phosphate-buffered saline solution. Using micropipette, the solution was retrieved and dropped upon a petri dish containing Brain Heart Infusion broth. The dish was then stored in an incubator for 24 hours, prior to counting the number of bacteria existed. The same methods were used to the rest of the patients, with total 128 molar bands from 32 patients. Results: There was a profound difference in numbers of bacteria found between those methods of sterilization. However, there was a non significant difference between the two groups which were at the alcohol-steam autoclave group and at the ultrasonic cleaning bath-steam autoclave group. Conclusion: This study showed that steam autoclave is better than for sterilizing molar band, as it left the minimal amount of bacteria in post-fitted molar band.Latar belakang: Molar band merupakan suatu alat penjangkaran yang dapat mengalami kontaminasi selama proses fitting band, sehingga perlu dilakukan suatu proses dekontaminasi untuk menghindari terjadinya cross-infection pada pasien. Tujuan: Penelitian ini bertujuan untuk mengetahui perbedaan jumlah bakteri pada molar band pasca fitting band setelah sterilisasi dry heat oven dan steam autoclave yang sebelumnya telah dilakukan pre-sterilisasi alcohol dan ultrasonic cleaning bath, sehingga dapat ditentukan metode sterilisasi yang terbaik dalam dekontaminasi molar band. Metode: Empat molar band yang telah melalui proses fitting band pada seorang pasien dibagi dalam dua kelompok. Pada kelompok pertama, dua molar band dilakukan pre-sterilisasi dengan alkohol, kemudian satu band dilakukan sterilisasi dengan dry heat oven dan satu band lainnya dengan steam autoclave. Kelompok kedua, dua molar band dilakukan pre-sterilisasi dengan ultrasonic cleaning bath, kemudian satu band dilakukan sterilisasi dengan dry heat oven dan satu band lainnya dengan steam autoclave. Molar band tersebut masing-masing kemudian dimasukkan ke dalam cairan phosphate-buffered saline, dengan micropipette cairan diambil dan dituangkan ke cawan petri yang berisi Brain Heart Infusion. Kemudian dimasukkan ke dalam inkubator selama 24 jam dan dihitung jumlah bakterinya. Metode yang sama dilakukan terhadap molar band lainnya, dengan total 128 molar band dari 32 pasien. Hasil: Terdapat perbedaan jumlah bakteri yang bermakna antara beberapa kelompok metode sterilisasi dan terdapat satu kelompok dengan perbedaan tidak bermakna, yaitu kelompok alcohol-steam autoclave dengan ultrasonic cleaning bath-steam autoclave. Simpulan: Hasil penelitian menunjukkan bahwa steam autoclave merupakan metode sterilisasi yang terbaik pada molar band yang telah melalui proses fitting band karena menunjukkan jumlah bakteri yang paling minimal.